2018
DOI: 10.1007/s00231-018-2346-y
|View full text |Cite
|
Sign up to set email alerts
|

Development of apple chips technology

Abstract: For develop of apple chips technology without chemical preservation osmotic dehydration in cherry or apple juice concentrates or fructooligosaccharide solutions and convection drying were used. Studies included the effect of dehydration on the mass transfer in apples and the quality of the final product. The temperature, type of osmotic solution and its concentration were changeable. The fruit were tested on mass transfer indicators, stability (water activity), texture (breaking test) and nutritional value (po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 24 publications
0
14
0
1
Order By: Relevance
“…The lowest value was observed in OD samples while the highest value was observed in ST samples. Pasławska et al [2017] and Kowalska et al [2018] reported similar phenomenon of TA value decrease after fruit immersion in a sugar solution. The changes in TA may be attributed to the elution of organic acids from tissue during OD process [Kowalska et al, 2018].…”
Section: Chemical Characterizationmentioning
confidence: 57%
See 1 more Smart Citation
“…The lowest value was observed in OD samples while the highest value was observed in ST samples. Pasławska et al [2017] and Kowalska et al [2018] reported similar phenomenon of TA value decrease after fruit immersion in a sugar solution. The changes in TA may be attributed to the elution of organic acids from tissue during OD process [Kowalska et al, 2018].…”
Section: Chemical Characterizationmentioning
confidence: 57%
“…Pasławska et al [2017] and Kowalska et al [2018] reported similar phenomenon of TA value decrease after fruit immersion in a sugar solution. The changes in TA may be attributed to the elution of organic acids from tissue during OD process [Kowalska et al, 2018]. Ascorbic acid and phenolic s are important nutritional or bioactive compounds in apples, and these chemicals are wellknown antioxidants that play an important role in promoting health [Loncaric et al, 2014;Blanda et al, 2008].…”
Section: Chemical Characterizationmentioning
confidence: 57%
“…The type of osmotic solution used for the initial dehydration and drying method significantly affected the color of the dried fruit ( Figure 6A). Regardless of the drying method, dehydration of quince fruit in sucrose solution (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and apple concentrate (17)(18)(19)(20)(21)(22)(23)(24)(25)(26) caused the least color changes; however, they changes could be clearly perceived by the human eye. Chips obtained as a result of preliminary dehydration in a sucrose solution looked attractive and those dehydrated in a chokeberry juice concentrate were very dark in color.…”
Section: Color Parametersmentioning
confidence: 99%
“…Fruit or vegetable snacks in the form of chips are often produced by drying [ 21 ]. These types of snacks do not require preservation with chemical substances.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to change your long-term eating habits and not achieve results in a short time. Weight reduction is mainly carried out by limiting food rations, cyclical meals and daily exercise [52,53]. Hope for better glycemic control is given by studies on the genetic reprogramming of human cells [54] and the possibility of using the batatrofin hormone [55].…”
Section: Treatmentmentioning
confidence: 99%